Analisis Kinerja Reactive Routing Protocol dalam Mobile Ad-Hoc Network (MANET) Menggunakan NS-2 (Network simulator) - Olivia Kembuan; Widyawan; Sri Suning Kusumawardani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
Mobile Ad-Hoc Network (MANET) is the type of network that can connect people without depending on fixed infrastructure. Dynamic topology that characterizes this network leads to different routing process compared to wired-network with fixed topology. The two main classes of routing protocols for mobile ad-hoc networks (MANETs) are proactive and reactive (or on-demand). Reactive routing protocols consume less bandwidth compared to proactive routing protocols because they establish the route on demand. This thesis presents the simulation results and performance analysis of reactive routing protocol Dynamic Source Routing (DSR) and Ad Hoc On-demand distance Vector Routing (AODV). The analysis is based on packet delivery ratio, routing overhead, average delay, and averagethroughput by varying the number of nodes and speed of nodes. The simulation is performed using NS2 network simulator. The results show that AODV outperforms DSR in more stress situations, however DSR outperforms AODV in less stressful situations (smaller number of nodes and lower speed of nodes). DSR produces higher delay in all scenarios, therefore this protocol not recommended for MANET with the need for low delay.